2022
DOI: 10.1111/pedi.13344
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric diabetes in China: Challenges and actions

Abstract: Pediatric diabetes is growing in China. The annual incidence of childhood type 1 diabetes is about 2.02-5.3 per 100,000 person-years. Type 2 diabetes in children and adolescents is increasing dramatically with the high-speed urbanization of China. The prevalence of type 2 diabetes varies from 1.64/100, 000 to 15.16/100,000 based on the geography and economy. Monogenic diabetes used to be underestimated in China and now more cases are emerging. In this review, we give an overview of pediatric diabetes in China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…Once a rare disease in youth, T2D is becoming more common and accounts for a significant proportion of youth onset diabetes in certain at‐risk populations. Worldwide incidence and prevalence of T2D in children and adolescents vary substantially among countries, age categories and ethnic groups 129–134 . The incidence and prevalence of T2D are highest among youth from a minority race/ethnicity, 99 likely because of many factors, including genetics, metabolic characteristics, cultural/environmental influences, and quality of and access to health care 135,136 …”
Section: Epidemiology Of T2dmentioning
confidence: 99%
“…Once a rare disease in youth, T2D is becoming more common and accounts for a significant proportion of youth onset diabetes in certain at‐risk populations. Worldwide incidence and prevalence of T2D in children and adolescents vary substantially among countries, age categories and ethnic groups 129–134 . The incidence and prevalence of T2D are highest among youth from a minority race/ethnicity, 99 likely because of many factors, including genetics, metabolic characteristics, cultural/environmental influences, and quality of and access to health care 135,136 …”
Section: Epidemiology Of T2dmentioning
confidence: 99%
“…The incidence of T1DM is increasing worldwide. Recent studies have shown that the overall population incidence of T1DM in China is 1.01 per 100,000 people per year [3], and the annual incidence of childhood with T1DM is about 2.02~5.3 per 100,000 [4]. The pathogenesis of T1DM has not been clearly defined so far, but it is generally thought to be due to multiple factors such as gene susceptibility and environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…The number of T1D children has increased sharply in recent years [ 29 ], how to face the risks from pandemic is a challenge for patients and their parents. A cross-sectional study involving 98 children and adolescents with T1D identified several key challenges faced by Iranian patients due to pandemic restrictions.…”
Section: Epidemiologymentioning
confidence: 99%